2020
DOI: 10.1111/jeb.13728
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of environmental, genetic and parental age at conception effects on telomere length in a wild mammal

Abstract: Understanding individual variation in fitness‐related traits requires separating the environmental and genetic determinants. Telomeres are protective caps at the ends of chromosomes that are thought to be a biomarker of senescence as their length predicts mortality risk and reflect the physiological consequences of environmental conditions. The relative contribution of genetic and environmental factors to individual variation in telomere length is, however, unclear, yet important for understanding its evolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 162 publications
2
35
0
Order By: Relevance
“…nestling collared flycatchers, Ficedula albicollis(h 2 =0.09, Voillemot et al, 2012), Seychelles warblers (h 2 =0.03-0.08, Sparks et al, 2021) and adult greater mouse-eared bats, Myotis myotis(h 2 =0.01-0.06, Foley et al, 2020), in which TL correlates with several weather variables. These studies also documented considerable year effects on TL (Foley et al, 2020;Sparks et al, 2021) similar to studies finding no heritability of TL in white-throated dippers (Becker et al, 2015) and European badgers (Meles meles , van Lieshout et al, 2021). In comparison, studies based on parent-offspring regression have often found higher TL heritabilities in e.g.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…nestling collared flycatchers, Ficedula albicollis(h 2 =0.09, Voillemot et al, 2012), Seychelles warblers (h 2 =0.03-0.08, Sparks et al, 2021) and adult greater mouse-eared bats, Myotis myotis(h 2 =0.01-0.06, Foley et al, 2020), in which TL correlates with several weather variables. These studies also documented considerable year effects on TL (Foley et al, 2020;Sparks et al, 2021) similar to studies finding no heritability of TL in white-throated dippers (Becker et al, 2015) and European badgers (Meles meles , van Lieshout et al, 2021). In comparison, studies based on parent-offspring regression have often found higher TL heritabilities in e.g.…”
Section: Discussionmentioning
confidence: 64%
“…years, range 1-8 years], n =388 fathers with n =1927 offspring) predicted TL in offspring from Hestmannoy and Traena. We applied within-subject centering (van de Pol & Wright, 2009) to separate within-parental age effects (e.g. senescence) from between-parental age effects (e.g.…”
Section: Parental Age Effects On Offspring Telomere Lengthmentioning
confidence: 99%
“…this study; Benetos et al, 2019;Bichet et al, 2020vs. Foley et al 2020Sparks et al, 2020;van Lieshout et al, 2020;meta-analysis: Kärkkäinen et al in prep). This is of relevance as TL repeatability sets, with exceptions, the upper limit to heritability (Dohm, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While telomere lengths in offspring have been shown to be affected by an offspring's environment (Dugdale and Richardson, 2018;Lieshout et al, 2021), effects of paternal age in birds have been found to be independent of this (Bauch et al, 2019;Boonekamp et al, 2014). As such, overall, there is growing support for at least contributory paternal inheritance of telomere length in some species of birds (Bouwhuis et al, 2018;Olsson et al, 2011;this study).…”
Section: Discussionmentioning
confidence: 79%